Aquifer depth determination of low permeability layers using geo-resistivity data: A case study of Enyigba mine area and environs, South Eastern Nigeria - Ekwe, Amobi; Azuoko, George-best; Iwuoha, Damian; Nkitnam, Elijah (Iraqi Journal of Science, 2022)
Many geophysical methods have been applied to locate groundwater in Nigeria’s rural and urban villages. Locating groundwater in low permeability formations like shales and siltstones is even more challenging due to the difficulty of mapping fracture zones within these formations. The fracture zones serve as potential aquifers in low permeability formations and have been the object of groundwater search in shales, siltstones and other low permeability formations. The electrical resistivity method has proven helpful in fracture mapping within low permeability formations due to the existing resistivity contrast usually observed between the fractured and non-fractured sections in the Shales and Siltstones. Three vertical electrical geosounding datasets (VES 1, VES 2 and VES 3) were acquired in the Schlumberger configuration, using a maximum current electrode spacing of 200m to delineate the fracture zones based on their electrical resistivities. The acquired datasets were processed and modelled using IP12 Win software, while the processed datasets were correlated with local geology to estimate the depths of the fractured shales in the area. Results show five modelled geo-electric layers with depths to the fractured shales ranging from 17-25m, while aquifer thicknesses range from 7 to 12m. Aquifer resistivities range from 58 - 115 ohm-m. The curves are primarily of the QH type. One of the Vertical Electrical Sounding Data points (VES 2) encountered an anomalously low resistivity zone at a depth range of 5 to 8m which was interpreted as a galena lode. The low resistivity zone has been confirmed through exploratory drilling to tie with Lead-Zinc lodes at a depth of 8m.